Interaction design from concept to completion - Steane, Jamie; Yee, Joyce (Bloomsbury Visual Arts, 2018)
Interaction Design explores common pitfalls, effective workflows and innovative development techniques in contemporary interaction design by tracking projects from initial idea to the critical and commercial reception of the finished project. The book is divided into six chapters, each focusing on different aspects of the interaction design industry. Each case study includes behind-the-scenes development design work, interviews with key creatives and workshop projects to help you start implementing the techniques and working practices discussed in your own interaction design projects. From immersive tourist experiences, to apps which make day-to-day life easier, the detailed coverage of the design process shows how strategists, creatives and technologists are working with interactive technologies to create the engaging projects of the future. -- Provided by publisher.